2017
DOI: 10.5430/wje.v7n3p14
|View full text |Cite
|
Sign up to set email alerts
|

Narrated Video Clips Improve Student Learning

Abstract: The purpose of this study is to determine whether viewing narrated video clips improves student learning. The study was conducted with undergraduate, mostly Biology majors, in an Animal Physiology course held in successive semesters. When both classes were given the same face-to-face lectures and identical online resources their performance on an exam with the same multiple choice questions was not statistically different (two-tailed, unpaired t-test). However, when one group was also given unlimited online ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In addition, movies give "a more concrete and realistic idea of the organs in place, in the body of the animal, compared to the diagrams provided in the ebook or lectures". This is in accordance with a previous study by Stephens who reported that 50% of his students used such videos as stand-alone mini-lectures for reminding them of concepts soon after lectures (Stephens 2017). Stephens considers videos a valuable guide to help students to reproduce experimental techniques.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, movies give "a more concrete and realistic idea of the organs in place, in the body of the animal, compared to the diagrams provided in the ebook or lectures". This is in accordance with a previous study by Stephens who reported that 50% of his students used such videos as stand-alone mini-lectures for reminding them of concepts soon after lectures (Stephens 2017). Stephens considers videos a valuable guide to help students to reproduce experimental techniques.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies on usefulness and students' perception of videos were reported for molecular biology (Dupuis et al 2013;Laneuville & Sikora 2015) and for physiology or anatomy teaching (Dobson 2009(Dobson , 2010Mayfield et al 2013). A study was also performed to establish whether viewing narrated biology/animal physiology videos could statistically improve results on multiple choice questions (Stephens 2017). Students' unstructured comments in our questionnaire allowed us to establish that videos help them "to focus on main criterion of each group of animal" to be dissected compared with all data provided by traditional lectures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation